Terminology of Leadership in the Quran On the Dimensions of Constitutional Law - Rohmah, Siti Ngainnur; Yunus, Nur Rohim (BULETIN ADALAH, 2024)
Leadership is a vital aspect of a country's social and political structure. Without effective leadership, a country is prone to experiencing chaos and instability. The Quran, as the sacred scripture of the Islamic community, provides comprehensive guidance on the concept of leadership. Terminologi seperti khalifah, imam, dan uli al-amr tidak hanya memberikan petunjuk spiritual tetapi juga memiliki relevansi praktis dalam konteks hukum tata negara. This article explores and explains how leadership terminology in the Quran might be applied in constitutional law, focusing on implementing principles of justice, responsibility, and community participation. The leadership terminology in the Quran provides a solid moral and ethical foundation for building a just, transparent, and effective governance. Concepts such as Khalifah, imam, and uli al-amr offer guidelines that can be used to ensure that leadership in governance reflects the values of justice, integrity, and the well-being of the people. Thus, the Quran serves as a spiritual guide and a crucial source of ethics and morals in forming a just state law.